Peningkatan Kemampuan Berpikir Kritis Menyimak Video Melalui Media Wordwall“Open The Box” Peserta Didik X C SMAN 5 Kupang: Improving Critical Thinking Skills in Video Listening Through Wordwall Media 'Open The Box' for Class X C Students of SMAN 5 Kupang - Sudirman; Burenia , Merlin Novayanti Nepa (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to improve students' critical thinking skills in listening to observation reports about certain cultural objects presented in video form. Based on the phenomena that occur, students are less critical in thinking and tend to look for shortcuts in critical thinking. The shortcut in question is that students prefer to describe the objects they observe according to the results of their research on online sites, so that the content and results of listening can be said to be different. The formulation of the problem in this research is how students' critical thinking capacity is when listening to videos. Learning is carried out using interactive media. The interactive media used is the wordwall application. The method used was classroom action research which lasted 2 cycles. This research began by testing the initial conditions, namely students' critical thinking abilities based on the results of watching videos. In cycle I it is related to the results of work in the listening process. The sample used was 36 students in class The research results obtained were that classical completion in the initial condition test of students' critical thinking ability only reached 11.11%, in cycle I critical thinking ability was 30.55% and in cycle II critical thinking ability was 80.55. Thus, classroom action research to improve students' critical thinking skills in listening using wordwall learning media was declared successful.